DIFFERENCE OF BOWEL SOUND RETURN TIME AMONG POST-LAPARATOMY SURGERY PATIENTS AFTER CHEWING GUM - Warisya Miftah Amanda; Chandra Isabella Hostanida Purba; Ristina Mirwanti (Belitung Nursing Journal, 2019)
Background: A surgical procedure using general anaesthesia in laparotomy surgery results in reduced bowel sound. A large number of patients who experience a delay in returning bowel sound after laparotomy surgery become the reason to give proper intervention in order to increase bowel sound return time. One of the non-pharmacological interventions that can be used is chewing gum. Objective: The purpose of this study is to identify the difference of bowel sound return time between groups of intervention and control after being given chewing gum intervention among post-laparotomy surgery patients. Methods: This quasi-experimental study used post-test only control group design. Thirty respondents were selected by purposive sampling technique. Data were collected through observation by calculating the bowel sound return time among post laparotomy surgery patients in the intervention group (n=15) and control group (n=15), and were analyzed using the Mann Whitney test. The intervention group was asked to chew the gum once for 30 minutes, and bowel sound was measured every 30 minutes for 120 minutes. Results: The results showed that bowel sound return time in the intervention group was 90 minutes and the control group was 150 minutes, and p-value was 0.005. Conclusion: There was a difference in the return time of bowel sound between the intervention and control groups. Therefore, the intervention of chewing gum could become one of the non- pharmacological interventions that can be considered in increasing the bowel sound return time among post-laparotomy surgery patients.